2017
DOI: 10.1159/000485387
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Guided Interstitial Laser Ablation for Intracranial Lesions: A Large Single-Institution Experience of 133 Cases

Abstract: mas, metastases, epilepsy foci, and radionecrosis. The rate of complications/unexpected readmission was 6.0%, and the mortality rate was 2.2%. With high-grade tumors, tumor volumes >3 cm in diameter trended toward a higher rate of complication (p = 0.056). Median progression-free survival (PFS) and overall survival (OS) for recurrent GBM were 7.4 and 11.6 months, respectively. As a frontline treatment for newly diagnosed GBM, median PFS and OS were 5.9 and 11.4 months, respectively. For metastases, median PFS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…The National Association of Epilepsy Centers annual surveys (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) reported that use of ATL for TLE decreased by more than 65% between 2006 and 2012 and extratemporal lobe surgeries comprised 38% of all resective surgeries in 2012. 17 Laser interstitial thermal therapy (LITT) is a minimally invasive surgical technique that has shown favorable outcomes in patients with a variety of brain lesions 16,18,26,27,[32][33][34] and has shown favorable outcomes in patients with epilepsy. 1,19,20,35,37,40 Following FDA clearance of two major LITT systems in 2007 (Visualase System, Medtronic Inc.) and 2009 (NeuroBlate System, Monteris Medical Corp.), this technology was first used to treat mesial TLE (mTLE) in 2010 and has been rapidly adapted as one of the neurosurgical tools to manage patients with RE.…”
mentioning
confidence: 99%
“…The National Association of Epilepsy Centers annual surveys (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) reported that use of ATL for TLE decreased by more than 65% between 2006 and 2012 and extratemporal lobe surgeries comprised 38% of all resective surgeries in 2012. 17 Laser interstitial thermal therapy (LITT) is a minimally invasive surgical technique that has shown favorable outcomes in patients with a variety of brain lesions 16,18,26,27,[32][33][34] and has shown favorable outcomes in patients with epilepsy. 1,19,20,35,37,40 Following FDA clearance of two major LITT systems in 2007 (Visualase System, Medtronic Inc.) and 2009 (NeuroBlate System, Monteris Medical Corp.), this technology was first used to treat mesial TLE (mTLE) in 2010 and has been rapidly adapted as one of the neurosurgical tools to manage patients with RE.…”
mentioning
confidence: 99%
“…Tissues at the periphery of the target or with high ablation thresholds may require unique trajectories or ablation parameters. Alternatively, a second laser catheter may be necessary [ 1 , 15 ]. By estimating tissue thermal responses a priori from preoperative imaging, it should be possible to improve outcomes by reducing frequency of missed ablations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, availability of normative cross-patient thermoablative properties would put us one step closer to being able to safely offer LITT without the need for real-time MRI monitoring of the ablation. In well-selected patients this could significantly decrease procedure duration without sacrificing safety, thereby reducing patient discomfort and risks of anesthesia and freeing up valuable hospital resources [ 15 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of complementary technologies, such as intraoperative magnetic resonance imaging (MRI) and real-time MRI thermometry has enabled LITT to enter the fields of neurosurgery and neuro-oncology ( 5 10 ). In recent years, LITT has been applied to intracranial lesions, including metastatic disease to the brain, and has yielded safe and satisfactory treatment results with significantly less morbidity ( 11 ) and shorter hospital stays than traditional open craniotomy ( 7 ).…”
Section: Introductionmentioning
confidence: 99%